Report of the Advisory Committee on Animal Husbandry and Dairying Volume I Main Report - Planning Commission (Planning Commission, 2010)
The Planning Commission, Government of India, vide its order No. Q.-13017/2/2008-Agri dated 4th February, 2009, constituted a Committee to look into the various developmental programmes followed in the Animal Husbandry & Dairy Sector and suggested measures for accelerating the growth rate with the objective of achieving the targets set for the 11th Plan. the constitution of the Committee and its term of reference have been annexed.
Planning Commission Government of India
Planning Commission Government of India